MRI-based quantification of residual fibroglandular tissue of the breast after conservative mastectomies. - Woitek, Ramona; Pfeiler, Georg; Farr, Alex; Kapetas, Panagiotis; Furtner, Julia; Bernathova, Maria; Schöpf, Veronika; Clauser, Paola; Marino, Maria A; Pinker, Katja; Baltzer, Pascal A; Helbich, Thomas H (Elsevier, 2018)
PURPOSE: Skin-sparing and nipple-sparing mastectomies (SSM; NSM) remove the breast's fibroglandular tissue (FGT), thereby reducing breast cancer risk. The postoperative presence of residual FGT (RFGT) is associated with remaining cancer risk. This study evaluated the role of MRI in the quantitative assessment of RFGT and its impact on the estimation of the remaining breast cancer risk. METHODS: The postoperative MRI scans (following EUSOMA recommendations) of 58 patients who had undergone SSM or NSM between 2003 and 2013, as well as preoperative MRI scans that were available in 25 of these patients, were retrospectively evaluated for the presence and location of RFGT by three radiologists. Two different observers quantitatively assessed the volume and percentage of retromamillary and other RFGT (RFGTrm and RFGTother) were assessed. The Fisher's exact test, the Student's t-test, and intraclass coherence were used to compare patient groups and to assess reproducibility. RESULTS: RFGT was found in 20% of all breasts and significantly more frequently after NSM than SSM (50% vs. 13%, p = .003). RFGTrm and RFGTother were more prevalent after NSM (p < 0.001; p = .127). RFGT ranged from 0.5 to 26% of the preoperative FGT, with higher percentages after NSM than SSM (p = .181). CONCLUSIONS: The prevalence and percentage of RFGT found on MRI indicate a considerable remaining postoperative breast cancer risk in some women.
Keywords: Breast cancer; Imaging; Magnetic resonance imaging; Mammary glands; Mastectomy; Adult; Breast Neoplasms; Female; Humans; Magnetic Resonance Imaging; Middle Aged; Neoplasm Recurrence, Local; Nipples; Organ Sparing Treatments; Patient Satisfaction; Postoperative Period; Prophylactic Mastectomy; Reproducibility of Results; Retrospective Studies; Risk Assessment